DETERMINATION OF DIAGNOSTIC ACCURACY OF BIOCHEMICAL PARAMETERS (CRP, LDH & FERRITIN) IN THE DIAGNOSIS OF COVID-19 IN SUSPECTED COVID CASES: Diagnostic Accuracy of Biochemical Parameters in COVID - Ashiq, Tayyaba; Sattar, Abdus; Uddin, Nasir; Bashir, Qamar; Shaheen, Sajida; Ijaz, Aamir (Pakistan Armed Forces Medical Journal, 2021)
Objective: To determine the diagnostic accuracy of the Lactate Dehydrogenase, C-Reactive Protein and Ferritin in suspected patients of COVID-19. Study Design: Cross-sectional validation study. Place and Duration of Study: Pathology department of Combined Military Hospital Lahore in the month of May 2020. Methodology: We included 101 adult (>18 years) symptomatic suspected COVID-19 patients of both genders. Children, pregnant women and asymptomatic patients were excluded from study. Age, gender and results of Reverse Transcriptase Polymerase Chain Reaction, Lactate Dehydrogenase, C-Reactive Protein, ferritin were recorded. Results: Lactate Dehydrodenase had highest sensitivity (75%) with positive predictive value of 71.6% and diagnostic accuracy of 65.3% among three biochemical parameters studied. Receiver Operator Characteristic curve was studied. Area under curve of Lactate Dehydrogenase (AUC=0.65) and Ferritin (AUC=0.59) reflected their ability to prognosticate the presence of COVID19 disease. However, C-Reactive Protein (AUC=0.42) appeared to be a poor predictor of the disease. Conclusion: Raised serum Lactate Dehydrogenase (>490 U/L) and Ferritin (>152 ng/L) levels can be used to predict the Reverse Transcriptase Polymerase Chain Reaction positivity for COVID-19 in the population of suspected patients of COVID19. However, C-Reactive Protein is a poor predictor of COVID-19.